FACTORS RELATED TO THE CAUSE OF TUBERCULOSIS (TB) IN CHILDREN - Ningsih, Nurna; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Tuberculosis (TB) is an infection brought about by the intricate living being Mycobacterium tuberculosis, which incorporates M. africanum, M. bovis, and M. canetti (and others that don't influence people). The aim of this research is to find out factors related to the cause of tuberculosis in children. This study reviews the literature using electronic data from several original studies. Online resources for finding literature include Science Direct and Google Scholar. keyword research used were "causative factor", "pulmonary TB", "child" Literature search was limited to the last 5 years in 201 8 to 2022 in Indonesian. Based on this search 4 articles were obtained with quantitative methods through the cass control approach. According to the findings from the literature analysis, a number of variables, including the patient's contact history, nutritional status, and environmental cleanliness, are linked to tuberculosis (TB) in children education and knowledge of parents, as well as BCG immunization and exclusive breastfeeding. Aspects such as the contact history of TB patients, nutritional status, environmental cleanliness, parental education and information, BCG vaccination, and exclusive breastfeeding are associated with the development of tuberculosis (TB) in childrent. is hoped that this article can help readers increase their knowledge about factors related to TB so that readers can take better care of themselves, their families and their environment to remain alert to the causes of TB disease. Keywords : causative factors, Children, Tuberculosis